Capital Flows and GDP in Emerging Economies and the Role of Global Spillovers - Joscha Beckmann; Robert Czudaj (Chemnitz University of Technology, Faculty of Economics and Business Administration, 2017)
This paper provides a global analysis of capital flow impacts on GDP for selected emerging economies. As additional control variables, we also include currency reserves and effective exchange rates in our analysis. We distinguish between gross and net capital flows and also assess the impact of both FDI and portfolio flows. Accounting for the fact that common factors have been the main drivers of capital flows while country-specific determinants (`pull' factors) drive the response to such shocks, we analyze shocks to country groups but consider country-specific responses based on a Bayesian time-varying panel VAR framework in the spirit of Canova and Ciccarelli (2009). Based on a sample of 24 economies, our results show a robust positive effect of capital flows on GDP. Except for Korea, both gross and net capital flows display a positive impact for around two quarters. The impact of effective exchange rates on GDP hardly offers an explanation for a possible transmission of capital flow effects with effective depreciations both positively and negatively linked to GDP. We also find that the effect of net portfolio flows is even more positive compared to net FDI flows for emerging economies. Finally, we provide evidence that the importance of global factors increases in times of crises.
Keywords: C32; F31; F32; 330; Gold; Bayesian econometrics; capital flows; exchange rates; FDI; Panel VAR